Spatial distribution and risk assessment of metal(loid)s in marine sediments in the Arctic Ocean and Bering Sea. (June 2022) - Zheng, Hui; Ren, Qiang; Zheng, Kaixuan; Qin, Zhikai; Wang, Yangyang; Wang, Yuguang
Abstract: Seventy-four surface sediment samples were collected from the Arctic Ocean and Bering Sea to determine the content of metal(loid)s (As, Cu, Cd, Ni, Pb, Zn and Cr). Metal(loid)s content in these sediments varied from 2.36–41.90 mg/kg for As, 8.63–82.28 mg/kg for Cu, 0.14–0.71 mg/kg for Cd, 11.86–100.60 mg/kg for Ni, 8.30–27.58 mg/kg for Pb, 39.93–391.43 mg/kg for Zn, and 40.96–106.49 mg/kg for Cr. The pH and water-soluble organic carbon content had considerable impacts on the content of metal(loid)s in sediment, but the texture of sediment has limited influence on metal(loid)s content in sediment. In addition, the hotspots of most of these metal(loid)s appeared in the Beaufort Sea region. The geoaccumulation index ( I geo ) indicated that Cd was the metal with the highest contamination in these sediments, with 55.41% of the sample sites posing moderate pollution. The ecological risk for As, Cu, Ni, Pb, Zn and Cr indicates low ecological risk (100%), while Cd posed moderate risk (35.14%), considerable risk (54.05%) and high risk (10.81%) and attributed more than 76.45% of the total potential ecological risk of these metal(loid)s. Highlights: Metal(loid)s content in marine sediments increased gradually in recent decade. Most of metal(loid)s accumulated in Beaufort Sea region Cd was the metal with the highest contamination in these sediments. Metal(loid)s in sediment posed low risk except for Cd.